Ewolucja metod badań zapachowych — początki osmologii w Polsce - Duniewska, Magda (Wydawnictwo Uniwersytetu Wrocławskiego, 2015)
In the article the author presents the origins of osmology in Poland, which date back to the early 1990s and which are inseparably connected with the formulation of guidelines considering the protection, storage and identification of human scent traces by means of the “K’’ method being an integral part of bylaw no. 19/92 of the Chief Commandant of the Police of the 12th of October 1992 concerning police dog services. The author analyses the content of the above document which contains, inter alia, information on the requirements of premises where research was carried out as well as guidelines on collecting and protecting scent traces. In addition, the principles for techniques of training police dogs and their handlers as well as adetailed description of osmological research are also included in the text. The author points out the first court ruling based on research results of scent traces and also emphasises the significance of performing numerous experiments for the development of osmology. The above mentioned experiments confirmed the efficacy of this method. The research included, inter alia, proving of impact of vinegar scent, cigarette smoke and cosmetics scent on the final result of an osmological examination. Simultaneously, the author underlines the fact that osmological expertise has been revolutionised since the early 90s. The knowledge about it is continuously deepened and techniques of carrying out such research are permanently being enhanced.
Keywords: osmologia; eksperyment; ślady zapachowe